POTENSI DAYA TARIK EKOWISATA SUAKA MARGASATWA BUKIT BATU KABUPATEN BENGKALIS PROVINSI RIAU - Muaz Haris; Rinekso Soekmadi; Hadi Susilo Arifin (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2017)
Bukit Batu Reserve Game (SMBB) is a core zone of The Biosphere Reserve of Giam Siak Kecil-Bukit Batu district that has potential to be developed as an ecotourism site. This study aimed to analyze the potential attractions of tourism object of SMBB by using observational methods and interviews. The analysis was performed based on the criteria in Rating Analsis Object operation (ADO-ODTWA), published by the Directorate General of Forest Protection and Nature Conservation (2003). The results showed that SMBB has decent potential to be developed with potential index of 86,2%. Potential of SMBB are as follows: rivers and lakes, flora and fauna, peatland, cottage and community’s plantation, Ekominawisata Research Station and Canopy tower, a Japanese research cottage, and village tour.